The formations of bare-stem, closed compound nouns in English - Purinanda, Faza Hannan (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2022)
Compounding is one of the most productive type of word formation processes in English and it is arguably the most controversial one in terms of its linguistic analysis. This paper aims at describing the formations of bare-stem, closed compound noun in English. This is a descriptive qualitative research, conducted by subclassifying the compound nouns into formations that are based on the word class of each element that constructs the compound. The result of the study shows that, firstly, there are thirteen formations from which bare-stem closed compound nouns can be constructed. Secondly, nouns, verbs, and adjectives can combine rather freely in compounding despite the patterns are not equally productive. This study also highlights the constraints in subclassifying compounds, which is a prevalent issue that has been widely recognized by scholars. Keywords: English morphology, compounding, noun, word formation